Efficacy of new technologies as teaching aids in morphological sciences. - María Teresa Martínez Barroso; Georgina Jiménez Estrada; Marta Gómez Arcila; Luis Orlando Pérez González (Medisur)
Background: Information society and new technologies have an impact on every part of educative process allowing the enlargement of teaching activities aimed to develop psychomotor, cognitive, emotional and social skills of teachers. Objective: To describe the effectiveness of new technologies in the teaching process of Morphological Sciences in the Medicine School in Cienfuegos. Methods: The results of final examinations of the first period of first course were analyzed in Anatomy I and Histology I. The investigation was carried out in all the students of first year of Medicine studies that belong to the project University Policlinic, the experimental group of this faculty and the traditional group. Results: Information and communication technologies as teaching aids help to improve the academic results of students.